Photosensitizers in antibacterial photodynamic therapy: an overview - Ghorbani, Jaber (Laser Ther, 2018)
Antibacterial Photodynamic therapy (APDT) is a process utilizing light and light sensitive agents (named photosensitizer (PS)) and is usually applied in an oxygen-rich environment. The energy of the photons is absorbed by the photosensitizer and subsequently transferred to surrounding molecules. Consequently, reactive oxygen species and free radicals are formed. These oxidative molecules can damage bacterial macromolecules such as proteins, lipids and nucleic acids and may result in bacterial killing. Unlike antibiotics, APDT as a novel technique does not lead to the selection of mutant resistant strains, hence it has appealed to researchers in this field. The type of PS used in APDT is a major determinant regarding outcome. In this review, various types of PS that are used in antimicrobial Photodynamic therapy will be discussed. PSs are classified based on their chemical structure and origin. Synthetic dyes such as methylene blue and toluidine blue are the most commonly used photosensitizers in Antibacterial Photodynamic therapy (APDT). Other photosensitizers including natural PSs (e.g. curcumin and hypericin) and tetra-pyrrole structures like phthalocyanines and porphyrins have also been studied. Furthermore, nanostructures and their probable contribution to APDT will be discussed.